Analisis Kesalahan dalam Penyelesaian Soal Cerita Pada Materi Perbandingan Ditinjau dari Perbedaan Gender - Ramdan Ramdan; Sudi Prayitno; Muh. Turmuzi; Baidowi Baidowi (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study aims to describe the problem-solving students of seventh-grade students in SMPN 24 Mataram the academic 2020/2021, it is solving comparative material story questions in terms of gender differences. This study is descriptive research. The sampling technique used was a population research technique and the research subjects selected in this study were 6 class VII students of SMPN 24 Mataram, consisting of 2 high-ability students, 2 moderately capable students, and 2 low-ability students. The data collection techniques used tests and interviews. The results obtained in this study there are differences in errors made by male and female students, while the most mistakes in the types of understanding error with a percentage of 75,48% in the high category. Meanwhile, female students made the most mistakes in the types of process skill errors with an error percentage of 62,11% high category. It is because at the stage of understanding many male students do not write down what they know and asked in the question, as the same time many female students do not know the correct completion procedure because they do not know the formula/method used to continue solving the problem.